Scientific Opinion on application EFSA‐GMO‐NL‐2013‐119 for authorisation of genetically modified glufosinate‐ammonium‐ and glyphosate‐tolerant oilseed rape MON 88302 × MS8 × RF3 and subcombinations independently of their origin, for food and feed uses, import and processing submitted in accordance with Regulation (EC) No 1829/2003 by Monsanto Company and Bayer CropScience. (10th April 2017) - ; Naegeli, Hanspeter; Birch, Andrew Nicholas; Casacuberta, Josep; De Schrijver, Adinda; Gralak, Mikołaj Antoni; Guerche, Philippe; Jones, Huw; Manachini, Barbara; Messéan, Antoine; Nielsen, Elsa Ebbesen; Nogué, Fabien; et al.
Abstract: In this opinion, the GMO Panel assessed the three‐event stack oilseed rape (OSR) MON 88302 × MS8 × RF3 and its three subcombinations, independently of their origin. The GMO Panel has previously assessed the single events combined to produce this three‐event stack OSR and did not identify safety concerns; no new information that would modify the original conclusions was identified. The combination of the single OSR events and of the newly expressed proteins in the three‐event stack OSR does not give rise to food and feed safety and nutrition issues – based on the molecular, agronomic/phenotypic and compositional characteristics. In the case of accidental release of viable OSR MON 88302 × MS8 × RF3 seeds into the environment, the three‐event stack OSR would not raise environmental safety concerns. The GMO Panel therefore concluded that the three‐event stack OSR is as safe and as nutritious as its conventional counterpart and the tested non‐GM reference varieties in the context of the scope of this application. Since no new safety concerns were identified for the previously assessed two‐event stack OSR MS8 × RF3, the GMO Panel considered that its previous conclusions on this subcombination remain valid. For the two subcombinations MON 88302 × MS8 and MON 88302 × RF3 for which no experimental data were provided, the GMO Panel assessed the likelihood of interactions among the single events, and concluded that their different combinations would not raise safety concerns. These two subcombinations are therefore expected to be as safe as the single events, the previously assessed OSR MS8 × RF3, and OSR MON 88302 × MS8 × RF3. Since the post‐market environmental monitoring plan for the three‐event stack OSR does not include any provisions for two subcombinations not previously assessed, the GMO Panel recommended the applicant to revise the plan accordingly.